Synthesis of the complete trans-activation gene product of human T-lymphotropic virus type III in Escherichia coli: demonstration of immunogenicity in vivo and expression in vitro. - Aldovini, A (1986)
Human T-lymphotropic virus type III (HTLV-III) contains a gene (tat-III) the product of which activates the expression of viral genes in trans. We have expressed in Escherichia coli the complete tat-III-encoded protein as well as a truncated form that lacks three amino acids from the amino terminus. These proteins are recognized by sera of many, but not all, infected individuals including patients with acquired immunodeficiency syndrome (AIDS) or AIDS-related complex, as well as asymptomatic seropositive persons. Seropositivity for the tat-III protein does not appear to correlate with the clinical stage of HTLV-III-related disease. Antibodies raised in rabbits against the E. coli-produced protein detect the native protein (apparent molecular mass, 14.5 kDa) in a virus-producing cell line. A second protein (26 kDa), of unknown origin but viral related, is also specifically recognized by the immune serum.